Brain death and organ and tissue donation: perception by medical students - Almeida, Ana Cristina Cezar Sawaya; Domingueti, João Paulo Silva (Brazilian Journal of Transplantation, 2018)
Purpose: The organ and tissue transplantation is an alternative to treat various diseases, but the number of donors is low and the waiting lists are long. This deficit is also due to the lack of information by the population. Such information is a responsibility of health professionals who must provide assistance and guidance. In this context, it is necessary for medical scholars to be qualified about organ donation and medical education must provide such knowledge. Purpose: To analyze the knowledge of medical students regarding brain death and organ donation. Methods: A self-administered questionnaire containing 14 objective questions was voluntarily answered and without identification. The sample was composed by 240 academics from a medical school, randomly selected corresponding to 48.78% of the total students. The collected data was grouped according to their level to assess the interval between levels. Results: From the 240 students interviewed, 35% took part of classes or courses on the subject, and 59.16% self-assessed their knowledge on organ donation and transplantation as regular. However, 90% reported having knowledge on brain death. This understanding has increased according to medical graduation evolves. Considering post mortem donation, 90.83% would be donors and the main reasons for the refusal to donate are: fear, misinformation, religion and just do not want. Academics were also assessed on alive donor transplants, in which 91.66% would make a donation, but 46.16% were unaware risks. Conclusion: Medical students are well instructed as to relevant contents on transplantation, such as brain death, but the approach on donating organs and tissues is insufficient to the practice.